A Clinicoradiological Assessment following Surgical Intervention in Patients of Cervical Spondylotic Myelopathy: An Institutional Experience - Maneet Gill; Vikas Maheshwari; Arun Kumar Yadav; Rushikesh Gadhavi (Indian Journal of Neurosurgery)
Introduction To critically analyze the functional and radiological improvement in patients of cervical spondylotic myelopathy (CSM) who underwent surgical decompression by an anterior or posterior approach. Materials and Methods A retrospective study was conducted in a tertiary-level Armed Forces Hospital from June 2015 to December 2019. Preoperative assessment included a thorough clinical examination and functional and radiological assessment. The surgical decompression was done by an anterior or a posterior approach with instrumented fusion. Anterior approach was taken for single or two-level involvement and posterior approach for three or more cervical levels. The pre and postoperative neurological outcome was assessed by Nurick and modified Japanese Orthopaedic Association (mJOA) score along with measurement of canal diameter and cross-sectional area. Results A total of 120 patients of CSM who underwent surgical decompression were analyzed. Both the groups were comparable and had male predominance. A total of 59 patients underwent surgical decompression by an anterior approach and the remaining 61 patients by the posterior approach. Out of the 59 patients operated by the anterior approach, 30 (50.85%) underwent anterior cervical discectomy and fusion (ACDF); remaining 29 (49.15%) underwent anterior cervical corpectomy and fusion (ACCF). In the posterior group (n = 61), 26 (42.6%) patients underwent laminoplasty and the remaining 35 (57.4%) underwent laminectomy with or without instrument fusion. Sixteen patients out of these underwent lateral mass fixation and the remaining 19 underwent laminectomy. There was functional improvement (mJOA and Nurick grade) and radiological improvement in both subgroups, which were statistically significant (p < 0.0001). Conclusion A prompt surgical intervention in moderate-to-severe cases of CSM either by the anterior or the posterior approach is essential for good outcome.